Investigation of improvements to city areas of importance to the implementation of clean water - Milanie, Feby (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In the context of improving urban areas through clean water services, the provision and distribution of clean water systems are the primary focus of this research. The study aims to identify effective methods to enhance clean water services. Following the PRISMA guidelines for systematic reviews and meta-analyses, the study searched four major databases: Scholar, ResearchGate, Scopus, and Taylor & Francis Online. The search process used relevant keywords such as